Berberine promotes M2 macrophage polarisation through the IL-4-STAT6 signalling pathway in ulcerative colitis treatment - Kai Xiong; Jia Deng; Tinghui Yue; Wenting Hu; Xinglin Zeng; Tao Yang; Tianbao Xiao (Heliyon, 2023)
Aim: This study focusses on the anti-inflammatory and immune-modulatory roles of berberine (BBR) in ulcerative colitis (UC) treatment. Additionally, the underlying mechanisms of BBR were systematically explored. Methods: A 3% (w/v) dextran sodium sulphate (DSS) solution was used for establishing the mice UC model. M2 macrophage polarisation was induced in RAW 264.7 cells using interleukin 4 (IL-4), whereas M1 macrophage polarisation was induced using lipopolysaccharide. Colon length, colon mucosa damage index (CMDI), and haematoxylin–eosin (HE) staining were used to evaluate colon damage induced by DSS. M1/M2 macrophages in the colon tissue were identified using immunofluorescence (IF) staining with CD86+ or CD163+. M1/M2 macrophages in the abdomen were examined using flow cytometry. An enzyme-linked immunosorbent assay was conducted to identify M1/M2 macrophage supernatant biomarkers in RAW 264.7 cells. Western blotting, immunohistochemical staining, and real-time PCR were performed to investigate the potential mechanisms of BBR for treating UC in vivo and in vitro. Results: BBR was found to prolong colon length, ameliorate CMDI and alleviate the colon's pathological changes in UC mice. In DSS-induced UC mice, M1 macrophages predominated. BBR promoted M2 macrophages and suppressed M1 macrophages in the colon and abdomen of DSS-induced UC mice. Additionally, BBR significantly decreased M1-specific markers (IFN-γ and IL-1β) while increasing M2-specific markers (IL-10 and TGF-β) in the supernatants of RAW 264.7 cells. BBR upregulated the mRNA expression of IL-4, STAT6, and Chil3 while downregulating TNF-α, IFN-γ, and NOS2 expression in vivo. Moreover, BBR activated the downstream targets of the IL-4-STAT6 signalling pathway and enhanced the phosphorylation of STAT6 in vivo and in vitro to polarise M2 macrophage. Conclusion: In UC mice, BBR suppressed M1 macrophages while promoting M2 macrophages. M1 macrophage suppression and M2 macrophage activation were strongly correlated with the anti-inflammatory and immune-modulating activities of BBR. BBR induced the polarisation of M2 macrophages by activating the IL-4-STAT6 signalling pathway, which contributed to its therapeutic efficacy against UC.